The Effects of Graded Levels of Calorie Restriction: XVIII.Tissue-Specific Changes in Cell Size and Number in Response to Calorie Restriction. Issue 10 (26th May 2022) - Phillips, Daniel; Mathers, Hayleigh; Mitchell, Sharon E; Speakman, John R
Abstract: Calorie restriction (CR) without malnutrition increases the health and life span of diverse taxa. The mechanism(s) behind CR are debated but may be directly linked to body composition changes that maintain energy balance. During a deficit, energy is primarily obtained from white adipose tissue (WAT; utilized) while other tissues remain unchanged (protected) or grow (invested) relative to body mass. The changes in mass of 6 tissues from 48 male C57BL/6 mice following 3-month graded (10%, 20%, 30%, or 40%) CR or fed ad libitum for 12 or 24 hours a day were related to cell size (hypo/hypertrophy) and/or number (hypo/hyperplasia). Tissues studied were retroperitoneal and subcutaneous WAT, brown adipose tissue (BAT; utilized), lungs (protected), and stomach and cecum (invested). Methodology was based on number of nuclei/tissue equaling the number of cells. Extracted DNA was quantified and used to estimate cell numbers (total DNA/DNA per diploid nucleus) and size (tissue mass/nuclei number). WAT utilization was caused solely by hypotrophy whereas BAT utilization resulted from reduced cell number and size. WAT cell size positively correlated with circulating hormones related to energy balance, and BAT cell number and size positively correlated with body temperature. No changes were found in the lungs, consistent with their protected status, whereas hyperplasia appeared to be the dominant mechanism for invested alimentary-tract tissues. These findings indicate the pattern of change of cell size and number across increasing levels of short-term CR is tissue-specific.